Biomarker Responses, Gene Expression Alterations, and Histological Changes in Zebrafish (Danio rerio) After In Vivo Exposure to Polychlorinated Diphenyl Ethers - Ye, Chunmeng; Xiong, Wenli; Shi, Shuaishuai; Shi, Jiaqi; Yang, Wenhui; Zhang, Xuesheng (Frontiers in Physiology, 2022)
Polychlorinated diphenyl ethers (PCDEs) have been detected in various aquatic matrices, which pose potential threats to aquatic ecosystem security. In this work, both micro and macro analysis methods were used to assess the toxicity of PCDEs to zebrafish. Results indicated that after in vivo PCDEs exposure, the oxidative stress and related gene of Danio rerio were significantly changed. The higher concentration or longer exposure time could more severe oxidative stress in zebrafishs tissues. Compared with among the five tested compounds, more obvious changes in the level of oxidative biomarkers of lower-chlorinated PCDEs (4-mono-CDE and 4,4'-di-CDE) exposure groups were observed. The integrated biomarker response analysis and gene expression results also indicate a similar trend. Histopathological observation suggested that 4,4'-di-CDE could render liver nuclei enlargement and necrosis, hepatocyte vacuolation, and the development inhibition of ovarian cells. Transmission electron microscope photos showed that 4,4'-di-CDE caused organelle damage in the liver and ovary, including the rupture of endoplasmic reticulum, swelling of mitochondria, and condensation of chromatin in the liver and mitochondria disappeared significantly in the ovary. The degree of damage is enhanced with the increasing exposure doses. In addition, PCDEs also significantly altered vitellogenin content and related gene (vtg1) expression, suggesting that PCDEs may be estrogen endocrine disruptors. Overall, these results provided some valuable toxicological data of PCDEs on aquatic species. Keywords: Polychlorinated diphenyl ethers; Oxidative stress; Histological changes; Integrated biomarker response; Endocrine disrupting effects;